STATE ADJUSTMENT OF AGRICULTURAL SECTOR: CREDIT FIELD - Skoryk M.О. (The actual problems of regional economy development, 2016)
The article is about the credit provision for agricultural enterprises by banking institutions of Ukraine. It has been argued that banking sector is biggest financial contributor for agricultural entities. It has been proved that the essence of state adjustment for credit provision for agricultural business is to create a favorable credit provision policy with help of partial compensation of interest rates on loans of banking institutions. It has been reasoned that reducing credit provision for agricultural producers in time of the financial crisis was due to several factors. It has been proved that efficient management is impossible without replenishment amounts of financial resources to increase working capital and investment activities of economic entities and, hence, increase their profitability. It has been argued that replenishment is possible by attracting investment, which in turn will make it possible to replenish, renew fixed assets and increase profitability of businesses. It is necessary total participation of state regulators to address these issues. JEL: Q 14